How Undergraduate Students Capture English Impromptu Speech Challenge - Asti Gumartifa; Indawan Syahri (VELES Voices of English Language Education Society, 2022)
The practice of giving a speech or presentation in front of the class is a big challenge for students in English education majors. Students feel unable to speak directly or impromptu in English speech lectures. Thus, this study aimed to find out what were the problem factors that hinder students from practicing impromptu speech in classes. Samples in this study were the fifth-semester students in the academic year 2022/2023 majoring in English education at the University of Muhammadiyah Palembang. The study was qualitative and quantitative with a mixed-method approach. The research design utilized was a descriptive approach. The instruments used in this study were questionnaires and interviews. Twenty samples of students responded to the questionnaires and 12 of them were selected for further interview. Results of the interview and questionnaire showed most students did not have the confidence to give an impromptu English speech in the public because of the anxiety factor. Students were shocked and unable to think properly when presenting the speech without preparation. Therefore, students were hard to develop words into sentences, even the prepared sentences were lost as a result of that anxiety.